Management of Congenital Heart Disease: State of the Art-Part II-Cyanotic Heart Defects - P. Syamasundar Rao (MDPI AG, 2019)
In this review management of the most common cyanotic congenital heart defects (CHDs) was discussed; the management of acyanotic CHD was reviewed in Part I of this series. While the need for intervention in acyanotic CHD is by and large determined by the severity of the lesion, most cyanotic CHDs require intervention, mostly by surgery. Different types of tetralogy of Fallot require different types of total surgical corrective procedures, and some may require initial palliation, mainly by modified Blalock–Taussig shunts. Babies with transposition of the great arteries with an intact ventricular septum as well as those with ventricular septal defects (VSD) need an arterial switch (Jatene) procedure while those with both VSD and pulmonary stenosis should be addressed by Rastelli procedure. These procedures may need to be preceded by prostaglandin infusion and/or balloon atrial septostomy in some babies. Infants with tricuspid atresia require initial palliation either with a modified Blalock–Taussig shunt or banding of the pulmonary artery and subsequent staged Fontan (bidirectional Glenn and fenestrated Fontan with extra-cardiac conduit). Neonates with total anomalous pulmonary venous connection are managed by anastomosis of the common pulmonary vein with the left atrium either electively in non-obstructed types or as an emergency procedure in the obstructed types. Babies with truncus arteriosus are treated by surgical closure of VSD along with right ventricle to pulmonary artery conduit. The other defects, namely, hypoplastic left heart syndrome, pulmonary atresia with intact ventricular septum, double-outlet right ventricle, double-inlet left ventricle and univentricular hearts largely require multistage surgical correction. The currently existing medical, trans-catheter and surgical techniques to manage cyanotic CHD are safe and effective and can be performed at a relatively low risk.